Attachment and Rumination in Female Acute Myocardial Infarction Patients and Their Influences on Post-traumatic Stress Disorder - Juanli LI; Ping LIU; Qun LU; Ling BAI; Meili LIU (康复学报)
Objective:To explore the attachment and rumination in female acute myocardial infarction patients and their influences on post-traumatic stress disorder (PTSD).Methods:A total of 193 patients were recruited by convenience sampling. PTSD Cheeklist-Vivilian Version (PCL-C), Experiences in Close Relationships Questionnaire-Revised (ECR-R) and Event Related Rumination Inventor (ERRI) were used to collect data.Results:The PCL-C score was (33.68±5.85) with the incidence of PTSD symptoms of 29.02%. The average scores of attachment avoidance and attachment anxiety were (3.29±0.82) and (3.64±0.93) respectively. There was significant difference of PTSD level among different attachment types (F=13.648, P<0.01). The rumination score was (34.65±10.69). CCU hospitalized time, religion, attachment anxiety and invasive rumination could influence the PTSD level, which could explain 40.7%of the total variation.Conclusion:Health workers should pay attention to the early psychological intervention of female patients with myocardial infarction, discover and dredge their negative emotions timely. The families should be educated to pay enough attention and understanding to the patients with strong intimate relationship needs after discharge in order to reduce the psychological stress level and improve life quality.